2011
DOI: 10.1590/s0103-73312011000100018
|View full text |Cite
|
Sign up to set email alerts
|

Um estudo sobre as mães adolescentes Brasileiras

Abstract: O artigo analisa as mães-adolescentes, relacionando seus dados sociodemográficos com os rendimentos mensais dos domicílios onde vivem. Tratase de uma pesquisa quantitativa na qual se utilizaram dados secundários da Pesquisa Nacional por Amostra de Domicílios (PNAD) de 2001 e de 2008. Consideramse mães-adolescentes aquelas que já haviam tido filhos nascidos vivos à época das pesquisas, que estão sendo estudadas no que tange a seu comportamento reprodutivo; frequência à escola; anos de estudo; condição no domicí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 7 publications
0
7
1
12
Order By: Relevance
“…However, this percentage has increased considerably in families earning up to the minimum wage, which indicates a correlation between adolescent pregnancy and family income. This study also demonstrated that adolescent pregnancy affects the education level, particularly for those adolescent mothers who belong to the lowest social class (less than 30%), and concluded that dropping out of school and a lack of participation in the labor market are associated with both adolescent motherhood and the prior socioeconomic condition (3) .…”
Section: Adolescent Pregnancymentioning
confidence: 69%
“…However, this percentage has increased considerably in families earning up to the minimum wage, which indicates a correlation between adolescent pregnancy and family income. This study also demonstrated that adolescent pregnancy affects the education level, particularly for those adolescent mothers who belong to the lowest social class (less than 30%), and concluded that dropping out of school and a lack of participation in the labor market are associated with both adolescent motherhood and the prior socioeconomic condition (3) .…”
Section: Adolescent Pregnancymentioning
confidence: 69%
“…Considerando que a região Sudeste apresenta um dos melhores indicadores socioeconômicos do país, tal fato não seria o esperado, já que alguns estudos indicam que a gravidez na adolescência está associada a piores indicadores socioeconômicos (Chacham, Maia, Camargo, 2012;Novellino, 2011;Simões et al 2003) e que a sua repetição está relacionada a indicadores ainda piores que o das mães com somente um filho (Silva et al, 2011), necessitando, assim, de maiores investigações sobre o fenômeno.…”
Section: Resultsunclassified
“…No entanto, alguns estudos indicam que as precárias condições socioeconômicas e as oportunidades restritas precedem a gravidez/maternidade na adolescência (Duncan, 2007;Novellino, 2011;Ribeiro e Gualda, 2011;Silva et al, 2011 (Novellino, 2011;UNICEF, 2011).…”
Section: Maternidade Na Adolescênciaunclassified
See 2 more Smart Citations